Comparison between predicted and observed compressibility characteristics of treated soil using precompression and vertical drain - Zukri, Azhani (2010)
Prefabricated vertical drain, PVD with preloading is one of the widely used techniques to accelerate the consolidation process in ground treatment program. Sometimes, it is very difficult to choose proper design parameters during design stage. Therefore, back analysis from field records is a means to verify these design parameters. The purpose of this project is to evaluate the performance of ground improvement by pre-compression and vertical drain implemented for the construction of permanent campus of Universiti Tun Hussein Onn (UTHM), Parit Raja, Batu Pahat, Johor Darul Ta’zim by comparing the settlement design parameters between field and theoretical value. The anticipate magnitudes of settlements were calculated using Terzaghi’s one dimensional consolidation theory while the monitored settlements were evaluated using Asoaka’s method. The predictions of the total settlements with and without soil treatment had been made for three different zones. The time rate consolidation with the application of PVD was calculated using Hansbo’s solution adopting both vertical and radial consolidation effects. The back calculated coefficient of consolidation in horizontal direction, ch(back-cal) from Asoaka’s plot was performed using different time intervals and it was found that the longer time interval produced lower field coefficient of horizontal consolidation. The modified coefficient of horizontal consolidation, ch(modified) value also had been evaluated and it was concluded as ch(modified) = 0.22 ch (lab). This ch(modified) value would contribute to the formation of settlement curve resembling the actual settlement recorded from Asoaka’s plot. The ch(back-cal) value was about 1.04 to 3.59 m2/year. The value evaluated from dissipation test was found to be larger than ch(back-cal) value indicated that the smear effect was significant. However, this laboratory coefficient of horizontal consolidation, ch(lab) was in good agreement with normal assumption of ch = 2cv especially in Zone A while in Zone B and C the ratio was found to be 1 to 1.3. The ratio of ch(back-cal) over cv(lab) was found to be 0.27 to 0.96. The ratio of ch(modified)/ cv(lab) was in range 0.27 to 0.88 while the ratio of cv(field) / cv(lab) value was found to be 0.13 to 0.48. The correlation of coefficient of volume compressibility, mv(field) = 0.4 mv(lab) in Zones A and C, while the ratio was found to be 0.2 in Zone B. The compression ratio can be concluded as CR(field) = 0.03 CR(lab) and the compression index, Cc value can be summarized as Cc(field) = 0.03 Cc(lab) while the recompression index, Cr was found to be Cr (field) = 0.12 Cr (lab). This study shows that laboratory values were significantly higher than the field values.